SEMANTIC ANALYSIS OF METAPHORS OF SELECTED JAMES ARTHUR’S SONG - Istama, Nanda Rizka; Al-Anwar, Sylvia Febbryani; Aidil Syah Putra (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2024)
This research examines the use and significance of metaphors in the lyrics of James Arthur's songs. The research aims to identify and categorize the types of metaphors used and to interpret their meanings within the context of the songs. This research was designed in qualitative research. The study categorizes metaphors into three types: structural, orientational, and ontological. Based on research findings, the researcher found that ontological metaphors are the most frequently used, followed by structural and orientational metaphors. By exploring the metaphors in selected songs, the research found how metaphors convey complex emotional experiences and articulate themes of love, memory, safety, and loss. The technique of descriptive analysis was applied to analyze data by reading the data and identify the types of metaphor used in James Arthur's selected song lyrics. Data collection is conducted through document study and non-participatory observation. Primary data is derived from the song lyrics, while secondary data is gathered from related journals and resources. These results are expected to help English teachers to use metaphors in the teaching process, and using metaphors in class can be an effective way to expand students' vocabulary, besides that it can be material for consideration and support for future researchers.